Beta-lactam dosing in critically ill patients with septic shock and continuous renal replacement therapy - Ulldemolins, Marta (BioMed Central, 2014)
Although early and appropriate antibiotic therapy remains the most important intervention for successful treatment of septic shock, data guiding optimization of beta-lactam prescription in critically ill patients prescribed with continuous renal replacement therapy (CRRT) are still limited. Being small hydrophilic molecules, beta-lactams are likely to be cleared by CRRT to a significant extent. As a result, additional variability may be introduced to the per se variable antibiotic concentrations in critically ill patients. This article aims to describe the current clinical scenario for beta-lactam dosing in critically ill patients with septic shock and CRRT, to highlight the sources of variability among the different studies that reduce extrapolation to clinical practice, and to identify the opportunities for future research and improvement in this field. Three frequently prescribed beta-lactams (meropenem, piperacillin and ceftriaxone) were chosen for review. Our findings showed that present dosing recommendations are based on studies with drawbacks limiting their applicability in the clinical setting. In general, current antibiotic dosing regimens for CRRT follow a one-size-fits-all fashion despite emerging clinical data suggesting that drug clearance is partially dependent on CRRT modality and intensity. Moreover, some studies pool data from heterogeneous populations with CRRT that may exhibit different pharmacokinetics (for example, admission diagnoses different to septic shock, such as trauma), which also limit their extrapolation to critically ill patients with septic shock. Finally, there is still no consensus regarding the %T(>MIC) (percentage of dosing interval when concentration of the antibiotic is above the minimum inhibitory concentration of the pathogen) value that should be chosen as the pharmacodynamic target for antibiotic therapy in patients with septic shock and CRRT. For empirically optimized dosing, during the first day a loading dose is required to compensate the increased volume of distribution, regardless of impaired organ function. An additional loading dose may be required when CRRT is initiated due to steady-state equilibrium breakage driven by clearance variation. From day 2, dosing must be adjusted to CRRT settings and residual renal function. Therapeutic drug monitoring of beta-lactams may be regarded as a useful tool to daily individualize dosing and to ensure optimal antibiotic exposure.